Unveiling the Enigma: The Rare Non-Calcifying Variant of Calcifying Epithelial Odontogenic Tumor - L. Malathi; Radhika Sridharan; N Aravindha Babu; K. M. K. Masthan (Journal of Pharmacy and Bioallied Sciences)
Calcifying epithelial odontogenic tumor (CEOT), first identified by Jens Jorgen Pindborg in 1955, is a rare developmental odontogenic tumor, accounting for approximately 0.4% of all such tumors and most commonly occurring in the third and fourth decades of life. A 63-year-old man presented with a painful swelling in the right lower face, which had progressively enlarged over four months. Clinical and radiological findings revealed a dentoalveolar abscess with an osteolytic lesion mimicking involving the mandibular ramus and an impacted tooth. Histopathological examination confirmed CEOT. This case is notable due to its unusual presentation, mimicking dental osteomyelitis and occurring in an older individual, emphasizing the need for thorough diagnostic evaluation in atypical cases.